Blastomeres of 8-cell mouse embryos differ in their ability to generate embryonic stem cells and produce lines with different transcriptional signatures - Alonso-Alonso, Sandra; Esteve-Codina, Anna; Martin-Mur, Beatriz; Álvarez-González, Lucia; Ruiz-Herrera, Aurora; Santaló, Josep; Ibáñez, Elena (Frontiers in Cell and Developmental Biology, 2023)
Embryonic stem cell (ESC) derivation from single blastomeres of 8-cell mouse embryos results in lower derivation rates than that from whole blastocysts, raising a biological question about the developmental potential of sister blastomeres. We aimed to assess the ability of 8-cell blastomeres to produce epiblast cells and ESC lines after isolation, and the properties of the resulting lines. Our results revealed unequal competence among sister blastomeres to produce ESC lines. At least half of the blastomeres possess a lower potential to generate ESCs, although culture conditions and blastomeres plasticity can redirect their non-pluripotent fate towards the epiblast lineage, allowing us to generate up to seven lines from the same embryo. Lines originated from the same embryo segregated into two groups according to their transcriptional signatures. While the expression of genes related to pluripotency and development was higher in one group, no differences were found in their trilineage differentiation ability. These results may help to improve our understanding of the ESC derivation process from single blastomeres and cell fate determination in the preimplantation mouse embryos.